The Urgency of Studying Philosophy in Learning and Its Characteristics - Yuhanid; Muhammad Gugun Gunawan; Tamsik Udin (Penerbit Hellow Pustaka, 2026)
Initially, philosophy was referred to as the mother of science because philosophy was able to answer questions about everything and all things, both related to the universe and humans with all the problems in human life. From this statement, there is a close relationship between education and philosophy, because philosophy tries to formulate an image of humans and society, while education tries to realize that image. The formulation of human dignity and dignity along with their society determines the goals and methods of organizing education, on the other hand education is a process of humanizing humans. The philosophy of education is a critical and fundamental answer to various basic statements about education such as what, why, where to, and how and how of the education. This research adopts a qualitative approach with a focus on literature review to explore in-depth understanding related to the topic under study. Literature review was chosen as the main method because it allows researchers to summarize, evaluate, and synthesize existing knowledge from various written sources. The data sources used in this study include textbooks, articles and scientific journals. The data collection process is carried out through a literature study which involves several stages. First, the researcher identifies library sources that are relevant to the research topic. Next, these sources are accessed through libraries, online databases, or other sources. After that, a selection is made of the most relevant and high-quality sources for further analysis. Important data and information are then extracted from the selected sources and recorded in a structured format to facilitate analysis. The data analysis technique used is content analysis, which involves a series of systematic steps. First, the collected data is summarized and focused to simplify analysis. Next, the data is presented in the form of narratives, tables, or graphs to provide a clear picture of the research findings. The validity and accuracy of the data is ensured through source or method triangulation. The data that has been analyzed is then interpreted based on the relevant theoretical framework to provide in-depth meaning. Finally, conclusions are formulated based on the results of the data analysis that has been carried out. The urgency of the philosophy of education is to foster human understanding and awareness. The philosophy of education is very much needed for the Islamic concept or view of humans as creatures towards the process of happiness, both in this world and the hereafter. The Islamic view of humans can be described through Philosophy is very much needed in education, because in practice education cannot be separated from the philosophical foundation as a source that underlies educational practice. As an educator, one must be aware of the importance of studying and understanding the philosophy of education. Because an educator who understands the philosophy of education can understand their work and know what they will do in class. The philosophy of education is not only used as a reference for exploring ideas, but also functions as a learning medium, especially about how to apply these ideas more accurately. By understanding the philosophy of education, educators will understand how to think critically and creatively about what needs to be done to develop and advance education, and be able to test and develop critical and creative ideas according to the characteristics and conditions of the social context of students. The philosophy of education is very much needed for the Islamic concept or view of humans as creatures towards the process of happiness, both in this world and the hereafter. Philosophical thinking has special characteristics or features. Various books explain the characteristics of philosophical thinking with various characteristics of philosophy formulated into four kinds of properties explained as follows: first, skepticism which is meant in philosophy is in the first form, namely graduation. In relation to religion, the existence of truth is not doubted, what is doubted is the ability to obtain that truth. Second, communalism is the result of philosophical thought is the property of the general public. Third, Desintrestedness is that the philosopher is not in the status of defending, but explaining and changing it to an ideal condition. Fourth, Universalism means comprehensive, namely philosophizing is the right of all mankind in general. The difference with communalism is in the content. If communalism implies that the content/results of philosophical findings become the property of all human beings anytime and anywhere. Meanwhile, universalism speaks in terms of rights, namely that all humans have the right to conduct philosophical studies.